Exploring Effective Methods for Introducing Phonology to Beginner Learners: A Comprehensive Literature Review - Fahima Mashalani; Yani Lubis; Miftahul Jannah (Tinta Emas Institute, 2023)
The research aims to identify the best method for Introducing phonology to beginners. The author of this study defined vital terms such as phonology and instructional approaches after analyzing appropriate sources and previous research. It explained how to introduce phonology using qualitative methods. It also answers the discussion and the question,